2006
DOI: 10.1111/j.1540-8167.2006.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ventricular Repolarization in Patients with Transient Left Ventricular Apical Ballooning: A Case Control Study

Abstract: The present study is the first to demonstrate significant differences of QT interval modulation in patients with transient left ventricular AB and acute ST-segment elevation MI. Even though transient AB is associated with a significant QT interval prolongation, rate adaptation of ventricular repolarization (i.e., QT dynamicity) is not significantly altered, suggesting a differential effect of autonomic nervous activity on the ventricular myocardium in transient AB and in acute MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
0
9
0
7
Order By: Relevance
“…They observed that the QT interval as well as the depth of the T-wave had a 2-peaked time course, one occurring around days 2-3 and the other one occurring between days 14-21. Bonnemeier et al [20], in a case control study, demonstrated that patients with TC, unlike patients with reperfused anterior myocardial infarction, continue to show modulation of the QT interval with changes in the heart rate. So far, only one study has systematically analysed malignant arrhythmias in TC [21].…”
Section: Discussionmentioning
confidence: 99%
“…They observed that the QT interval as well as the depth of the T-wave had a 2-peaked time course, one occurring around days 2-3 and the other one occurring between days 14-21. Bonnemeier et al [20], in a case control study, demonstrated that patients with TC, unlike patients with reperfused anterior myocardial infarction, continue to show modulation of the QT interval with changes in the heart rate. So far, only one study has systematically analysed malignant arrhythmias in TC [21].…”
Section: Discussionmentioning
confidence: 99%
“…Neben sinuatrialen und atrioventrikulären Blockierungen und Vorhofflimmern [27,35,36,37,38] werden maligne ventrikuläre Rhythmusstörungen beobachtet. In Übereinstimmung mit einer bei TTC typischerweise vorhandenen QT-Verlänge-rung [13,38] können sich diese als Torsadede-Pointes-Tachykardien manifestieren [39,40,41]. Die berichtete Inzidenz von malignen ventrikulären Tachykardien liegt zwischen 1,5% und 15% [1,8,27,42].…”
Section: Rhythmusstörungenunclassified
“…Die Mehrzahl der Patienten beklagt Angina pectoris und Luftnot. Im Elektrokardiogramm finden sich mehrheitlich ST-Hebungen oder diffuse Veränderungen der T-Welle, in der Frühphase häufig auch eine Verlängerung der QT-Zeit [10,11,12,13]. Zahlreiche Fallserien belegen, dass ungefähr 1-2% der Patienten, die unter dem Bild eines ST-Elevationsinfarkts behandelt werden, an einer TTC leiden [1,7].…”
unclassified
“…Systemic sympathetic activation, elevated catecholamine concentrations and autonomic blockade have been shown to significantly prolong the QT inter- val. Furthermore, prolonged QTc in patients with TTC may also suggest regional sympathetic denervation resulting from direct myocardial damage or transient cardiac autonomic stunning caused by sympathetic hyperactivity [19,20]. Patients with TTC typically display clinical features resembling those of an acute coronary syndrome, therefore acute coronary angiography is indicated in most cases.…”
Section: Discussionmentioning
confidence: 98%